INFECTION AND PRE-TERM LABOR- A PROSPECTIVE CROSS-SECTIONAL STUDY. - Keshri, Renuka; Poojita; Choubey, Richa; Gumber, Akanksha (Student's Journal of Health Research Africa, 2023)
Background: Infections of the vaginal canal have been linked to an increased risk of preterm labor. Prenatal screening for genitourinary infections, particularly in high-risk cases, prompt recognition, and treatment reduce the incidence of premature labor. Methods: From January 2021 to December 2022, a cross-sectional study was done in the Department of Obstetrics and Gynaecology at Narayan Medical College and Hospital in Jamuhar, Sasaran, Bihar. A detailed clinical history was collected, including the patient's age, level of education, duration of antenatal care, parity, and obstetrical history. There was a general examination, a systemic examination, and an obstetric examination. Hb, total leucocyte count, blood sugar, blood grouping, HIV, HBsAg, and VDRL tests were performed. Results: The prevalence of UTI in preterm labor was 30.1% in 264 cases of preterm labor investigated. The majority of responders (49.4%) were between the ages of 25 and 29. In 77.2% of cases, the patients were booked. UTI was shown to be more common in multipara in my study. The prevalence of UTI in illiterates was 92.4%. The majority of responders were late preterm, with gestational ages ranging from 34 to 37 weeks. E. coli was the most often isolated organism in urine culture. Conclusion: To avoid difficulties, all pregnant women should be evaluated for UTI, treated with suitable antibiotics if the culture is positive, and then retested for cure. Furthermore, providing health information to all pregnant women, particularly those from low socioeconomic backgrounds, will aid in the prevention of urinary tract infections. Recommendation: Checking for infections in pregnant women needs to be done in order to avoid infections before labor. Patients need to be given antibiotics in preterm labor to stop group B streptococcal transmission.